OPTIMIZATION OF BEVERAGE COST CONTROL IN HOTELS THE ONE LEGIAN - Sukma Suryani, Anak Agung Istri; Crisna Wijaya, Gede (LPPM Univ. Ibn Khaldun Bogor, 2023)
During the transition from a pandemic to an endemic period, the costs incurred by the hotel became unstable because during this transition the hotel was making adjustments, so between the existing standard costs and the actual costs, there were still deviations. The cost beverage standard applied to the actual cost of beverage has a difference that can be detrimental and have an impact on hotel revenue. The location of the fieldwork practice is at The One Legian Hotel. What is discussed is Optimizing Beverage Cost Control at The One Legian Hotel during the Transition of the Pandemic Towards Endemic. The problems encountered at The One Legian Hotel are (a) supplier selection, (b) a spike in raw material prices (c) uncertainty in room occupation (d) competitors selling the same product. Efforts that can be made to overcome these problems are by preparing reserve suppliers, creating attractive promos, and maintaining stable selling prices.